Real-world treatment patterns, patient-reported outcomes, and effectiveness of flexible-dosing etanercept in patients with plaque psoriasis in Greece - Dimitris Rigopoulos; Aikaterini Patsatsi; Christina Antoniou; Dimitrios Sotiriadis; Angeliki Roussaki-Schulze; Nadia Boubouchairopoulou; Ioannis Skiadas; Vasillios Tsekouras; Ana Cristina Hernandez Daly (Dermatology Reports, 2022)
Etanercept is approved for continuous or intermittent use and flexible dosing in plaque psoriasis (PsO). The objectives of this study were to investigate real-world treatment patterns with etanercept in Greek adults with moderate-to-severe PsO. This non-interventional multicenter study included a retrospectiveto- prospective (RP) cohort, previously treated with etanercept for ≥24 months and followed for an additional 6 months, and a biologic-naïve, prospective-only (PO) cohort, followed for 6 months after treatment initiation. Parameters assessed included Psoriasis Area and Severity Index (PASI), percentage of body surface area (BSA) affected, Dermatology Life Quality Index (DLQI), and adverse events (AEs). This study enrolled 123 patients (RP, n = 56; PO, n = 67), who mostly adhered to continuous treatment (RP, 68%; PO, 95%). The two cohorts had similar mean baseline-to-endpoint decreases in PASI (-9.5 vs -10.1) and BSA (-11.9 vs -12.3). The PO-CTP population had a mean DLQI baseline-to-endpoint score decrease of -5.8, which was statistically significant and clinically meaningful. Treatment-emergent AE rates were 58.9% (RP) versus 26.9% (PO). These real-world data suggest a similar effectiveness of continuous and intermittent etanercept treatment in Greek patients with PsO.